Perencanaan Perawatan Mesin Untuk Menurunkan Biaya Perawatan Dengan Menggunakan Metode Markov Chain - Wahyu Eni, Henry Susiawan (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
For this time, machine and tools are much wear in some factory to support human in produce something. And so machine and tools it self are an object which be able to damaged, then be needed to take care of those thing in a continue manner. In a logic manner could be arithmeticed that with continued machine treatment will more decrease the cost of factory every periode than the consequence cost of machine damage. Especially in order to get a good productivity, good quality and low cost level, so one of method to prevent this thing is using Markov Chain method. Base on result analyst, then known that the treatment of Root Washer machine are Korective Treatment Planning on weight status and Prohibition treatment on light in weight and average status. Then the treatment cost motion on Root Whasher machine have a cost judgment result Rp. 492.977,-